Saving the planet by design reinventing our world through ecomimesis - Yeang, Ken 1948- (Routledge, 2020)
Can we save the Planet'? For a resilient, durable and sustainable future for human society, we need to repurpose, reinvent, redesign, remake and recover our human-made world so that our built environment is benignly and seamlessly biointegrated with Nature to function synergistically with it. These are the multiple tasks that humanity must carry out imminently if there is to be a future for human society and all lifeforms and their environments on the Planet. Addressing this is the most compelling question for those whose daily work impacts on Nature, such as architects, engineers, landscape architects, town planners, environmental policy makers, builders and others, but it is a question that all of humanity needs to urgently address. Presented here are two key principles as the means to carry out these tasks - ecocentricity' being guided by the science of ecology, and ecomimesis' as designing and making the built environment including all artefacts based on the emulation and replication of the ecosystem' concept. Designing with ecology is contended here as the authentic approach to green design from which the next generation of green design will emerge, going beyond current use of accreditation systems. For those who subscribe to this principle, this is articulated here, showing how it can be implemented by design. Adopting these principles is fundamental in our endeavour to save our Planet Earth, and changes profoundly and in entirety the way we design, make, manage and operate our built environment